2014
DOI: 10.1007/s00520-014-2447-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospice care on survival and cost saving among patients with liver cancer: a national longitudinal population-based study in Taiwan

Abstract: Hospice care did not significantly affect survival, and hospice patients had lower per-patient expenditures and were less likely to require high-cost medical care than their non-hospice counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 24 publications
(30 reference statements)
4
40
0
Order By: Relevance
“…Relatively higher survival rates were observed in younger patients (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) compared with older patients (65-74, 75+), particularly for sites including the stomach, lung, pancreas, B and CNS, blood (NHL) and cervix. Cancer of the oesophagus, female breast and bladder had higher survival in middle-aged groups (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively higher survival rates were observed in younger patients (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) compared with older patients (65-74, 75+), particularly for sites including the stomach, lung, pancreas, B and CNS, blood (NHL) and cervix. Cancer of the oesophagus, female breast and bladder had higher survival in middle-aged groups (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)…”
Section: Resultsmentioning
confidence: 99%
“…The survival for patients with liver cancer is usually poor. A report from Taiwan revealed that the mean survival time of 3,850 patients with liver cancer was ~1.8 years (53). An American study demonstrated that the 5-year relative survival was 3% in the period from 1975-1977, 5% from 1987-1989 and 18% from 2003-2009 (50).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, compared with patients receiving usual care, hospitalized patients with HCC receiving hospice care had a shorter LOS (8 versus 14 days) and 3‐fold fewer invasive procedures, received more medication for pain, and had nearly a 3‐fold lower daily cost of care . Nationwide experience from Taiwan showed that patients with HCC referred to hospice had equivalent survival and 12% lower cost of care over the last month of life compared with those receiving usual care, lower incidence of ICU admission (3% versus 18%) and cardiopulmonary resuscitation (CPR) with intubation (1% versus 16%), and less frequent in‐hospital death (0% versus 45%) . Comparable data from the United States showed a reduced prevalence of emergency department use (6% versus 16%), hospital admission (8% versus 48%), ICU admission (3% versus 25%), and in‐hospital deaths (4% versus 58%) among patients with HCC referred to hospice .…”
Section: The Benefits Of Pc In Esldmentioning
confidence: 99%
“…In Israel it is called as "hospital at home", in the US "home care", "home health care", "home nursing" while "home health care" or "home visiting"' is used in East of Europe. In France, "home care-fin de vie"' is used to describe [4].…”
Section: Evaluation Of Home Care Services At a Training And Research mentioning
confidence: 99%
“…It is the palliative care option that provides benefits for the dying person by not only limiting exposures of health risks of staying in a hospital but also having the opportunity of decrease the total health care costs [4]. The specialty of palliative medicine arose throughout the hospice movement.…”
Section: Evaluation Of Home Care Services At a Training And Research mentioning
confidence: 99%